A relational approach to landscape and urbanism: the view from an exclusive suburb. (3rd April 2017) - Mitchell, Don
Abstract: This paper promotes a relational (that is, dialectical view) of landscape urbanism through the examination of an exclusive, racialised Northern California suburb as it has developed in relationship to—and cocooned itself from the problems and disamenities of—the broader urban region. Through the case of the wealthy, mostly white town of Moraga, it suggests that landscape studies must be attentive to the larger regional dynamics that produce and reproduce specific places. The argument is both intellectual and political: to the degree that the recent turn to discourses of and practices concerning 'the right to landscape' are inattentive to how landscapes are produced, unjustly, through their regional others, then to that degree the right to landscape threatens to reproduce injustice, not overcome it. Thus, the paper argues that any discourse and struggle for the right to landscape must be conjoined with a struggle for the right to the city. It suggests that the right question to ask of the landscape is not so much 'whose landscape' (as much work on the right to landscape has it), but 'landscape for whom.'